Consenso estratégico nas operações: percepções gerenciais sobre as prioridades competitivas - Zanon, Celeste José (Universidade Federal de São Carlos, 2005)
This research concentrates in the analysis of the strategic consensus in operations, having as starting point the perceptions of the competitive priorities of managers, middle managers and technical managers. These professionals work in marketing, sales, product development and manufacturing areas. The word consensus is defined as the similar understanding of these managers regarding the importance and the performance of the strategic priorities. The case study method was adopted due to the necessity of examining the operations strategy in the intra-plant basis, through the perceptions in different functional areas of one same company. It aimed to understand the deficiencies of such strategy through a meticulous investigation in one of the establishments of a corporation that is world widely known in the writing, painting and cosmetics businesses. The use of the Importance-Performance matrix of Slack (1993) as an analytical instrument, and the development of a methodology that will interrelate the perceptions with the functions and the hierarchical levels, allowed this work to contribute to the business unity researched through the divergences noticed in the priorities order, through the inconsistent perceptions on the disaggregated priorities, through the relative dispersions of the perceptions between functions and levels; ultimately, through the understanding of how the operations strategy is interpreted in the company. The practical relevance is presented by the inferences that considerably influence the perception of the competitive priorities, and which can improve the practice in other companies, making them aware of the importance of the strategic consensus in the operations: the organizational protection that contributes to determine the interaction/intermediation ratio; the accessibility of information, especially those relating to competitors, the non-communicating of objectives, the inability to operationalize the strategy through the disaggregated priorities management and the products manufacturing policies make-to-stock, make-to-order, assembled-to-order, etc. Ultimately, besides the utilized methodology and the assessment of the consensus extended to middle management and to technical management, the research also contributes to the knowledge of the operations strategy area, proposing the systematization of the integration of activities that will promote consensus in managing the competitive priorities, since that is a challenge to the whole hierarchy of strategies, being of main importance to attain a sustainable success in its implementation. The following steps are suggested: the contextualization of a reality, the exploration of perceptions of such reality; the suppositions that orientates investigations; the search for reliable information; the birth of new perceptions; the discussion of the trade-offs; the negotiating of an explicit collective consensus, and the checking of this consensus among the social actors.
Keywords: Empresários; Estratégia de operações; Prioridades competitivas; Strategic consensus; Operations strategy; Competitive priorities; ENGENHARIAS::ENGENHARIA DE PRODUCAO